Islamic financial inclusion and sustainability mindset: Pathways to MSME performance and SDG achievement - Iman Supriadi; Rahma Ulfa Maghfiroh; Rukhul Abadi (Alkasb: Journal of Islamic Economics, 2025)
The growth of micro, small, and medium enterprises (MSMEs) is crucial for Indonesia’s economic and environmental sustainability. However, little is known about how Islamic financial inclusion and sustainability mindsets work together to enhance sustainable business performance in this sector. This study explores the combined impact of Islamic financial inclusion and sustainability mindset on the financial sustainability of East Java’s MSMEs, with green entrepreneurial orientation as a mediating factor. Using a quantitative approach, data was gathered from 115 sharia-compliant MSMEs through structured surveys and analyzed using Structural Equation Modeling (SEM). The results confirm that both Islamic financial inclusion and a sustainability mindset positively influence sustainable financial performance, with green entrepreneurial orientation playing a partial mediating role. Interestingly, the strength of these relationships varies depending on business models. The study bridges Islamic finance principles with sustainability theories, offering empirical evidence for policymakers designing Islamic finance initiatives to support MSME sustainability. It also emphasizes the need for MSMEs to integrate financial accessibility with eco-conscious thinking. These findings contribute to the ongoing discussion on aligning Islamic finance with sustainable development in emerging markets, providing practical guidance for businesses and regulators alike.